2014
DOI: 10.1016/j.amepre.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Periodontal Therapy on General Health

Abstract: These cost-based results provide new, independent, and potentially valuable evidence that simple, noninvasive periodontal therapy may improve health outcomes in pregnancy and other systemic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(61 citation statements)
references
References 12 publications
1
54
1
5
Order By: Relevance
“…Periodontitis is a public health problem in developed countries, with direct and indirect medical consequences and costs that can justify public health policies (Bouchard, Boutouyrie, Mattout, & Bourgeois, 2006;Jeffcoat, Jeffcoat, Gladowski, Bramson, & Blum, 2014;Kassebaum et al, 2014). Thus, epidemiological surveillance of periodontal diseases, especially of severe periodontitis, is of particular importance.…”
Section: Discussionmentioning
confidence: 99%
“…Periodontitis is a public health problem in developed countries, with direct and indirect medical consequences and costs that can justify public health policies (Bouchard, Boutouyrie, Mattout, & Bourgeois, 2006;Jeffcoat, Jeffcoat, Gladowski, Bramson, & Blum, 2014;Kassebaum et al, 2014). Thus, epidemiological surveillance of periodontal diseases, especially of severe periodontitis, is of particular importance.…”
Section: Discussionmentioning
confidence: 99%
“…The increased prevalence of cardiovascular disease,27,28 hypertension,25 and stroke in periodontal disease25,29 has been attributed to a common susceptibility hypothesis, that of direct bacterial invasion of blood vessels, and/or a systemic inflammatory response leading to increased circulating cytokines that damage vascular endothelium 30. Importantly, treating periodontitis in patients with common comorbidities has shown to be an effective way of reducing both financial costs and admissions for cardiovascular disease and diabetes mellitus,31 lending credence to this hypothesis. Thus, both periodontitis and COPD occur with a similar spectrum of comorbid disease.…”
Section: Periodontitismentioning
confidence: 99%
“…The MEPS collects detailed information about medical and dental visits, health insurance, expenditures, and payments as well as socio‐demographic characteristics of the US community‐based population. MEPS respondents are interviewed five times over a 2‐year period . Persons in our sample were restricted to those with positive‐valued population weights in both years they were in the MEPS, so we excluded persons in their first year in the survey in 2014 and in their last year in the survey in 2008.…”
Section: Methodsmentioning
confidence: 99%
“…With the exception of RA, those completing treatment for PD had statistically significant reductions in medical costs and hospitalizations over the 5-year period. 13 A recent study estimated cost savings of $63.5 billion to Medicare beneficiaries with heart disease, diabetes, or stroke by hypothetically offering coverage for periodontal care including an initial treatment and follow-up annual maintenance visits over the period 2016-2025. 14 A study using 2002 Medicare Current Beneficiary Survey data found higher cost nonpreventive dental use and expenditures for Medicare dental patients who did not receive preventive oral services compared to those who did receive preventive care.…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation